Preliminary Evaluation of a Breast Cancer Screening Shared Decision-Making Aid Utilized Within the Primary Care Clinical Encounter - Lori DuBenske PhD, MS; Viktoriya Ovsepyan BA; Terry Little MS; Sarina Schrager MD, MS; Elizabeth Burnside MD, MPH, MS (Journal of Patient Experience, 2021)
Introduction: The US Preventative Services Task Force recommends shared decision-making (SDM) between women aged 40 and 49 years and their physician regarding timing of mammography screening. This preliminary study evaluates women’s and physician’s satisfaction using Breast Cancer Risk Estimator & Decision Aid (BCARE-DA), a shared decision aid utilized during the clinical encounter, and examines SDM quality for these encounters. Methods: Fifty-three women and their physician utilized BCARE-DA and completed surveys measuring satisfaction with Likert-type and open-ended items and women completed the Decision Conflict Scale. Clinic visit transcripts were evaluated for SDM quality using Observer OPTION-5 and Breast Cancer Screening Decision Core Components Checklist. Results: Women and physicians positively evaluated BCARE-DA. Women had low decision conflict. Physicians demonstrated moderate effort toward SDM, greatest in offering options, and lowest for team talk. Physicians demonstrated 2/3 of core SDM elements in 80% to 100% of encounters. Conclusion: Preliminary findings suggest specific promise for such Decision Aids to facilitate SDM through understanding of personal risks for breast cancer formulated within each screening option, while some SDM elements likely require additional facilitating.